INVESTIGASI PERBEDAAN SUHU TUANG TERHADAP SIFAT MEKANIK DENGAN PENGUKURAN KEKERASAN DAN IMPACT PADA PADUAN AL 2024 - R. Syaputra; D. P. Ali; R. Eko; H. Akhyar; P. T. Iswanto (ROTOR, 2016)
Aluminum alloys have high strength to weight ratio, tough enough, resist to fatigue crack propagation, easy to cast, corrosion resistant and recycle. High strength to weight ratio means an efficient, strong and capable of long-lived, economical and environmentally friendly. In the application as a frame structure, mechanical properties are something that must be considered. Therefore, the researchers tried to find the effect of pouring temperature differences in Aluminum 2024 through hardness test and impact test. For the investigation at three different temperatures of 688oC, 738oC, 788oC, the gravity casting method is used to produce a plate-shaped object. The test results showed an increase in hardness, with the highest value of 103.71 BHN at a temperature of 738°C and impact test results with the highest value of 4.9 Joule at temperatures of 738°C. Keywords: aluminum alloy 2024, foundry, cast temperature